Inhibition of bacterial adherence to host tissue does not markedly affect disease in the murine model of Pseudomonas aeruginosa corneal infection. - Zaidi, T S (1997)
The prevention of bacterial infections by the inhibition of binding to host tissues is an oft-touted approach, but few studies with appropriate models of infection have tested its feasibility. Pseudomonas aeruginosa causes severe corneal infections in mice after inoculations with low doses, and infection is thought to depend upon an initial adherence of the bacteria to corneal cells. In vitro, adherence to corneal cells is mediated to a large degree by the complete-outer-core oligosaccharide of the bacterial lipopolysaccharide (LPS). However, bacteria adhering to tissues in vivo are difficult to differentiate from nonadherent bacteria. Since a direct correlate of P. aeruginosa adherence to corneal epithelial cells is the degree to which these cells internalize P. aeruginosa, the level of adherence in vivo can be approximated by measuring P. aeruginosa ingestion by cells by using gentamicin exclusion assays. To determine the degree to which inhibition of the corneal cell adherence affects the course of infection and disease in the murine model, we evaluated the ability of LPS-outer-core oligosaccharide to inhibit bacterial association and entry into corneal cells and to modulate the development of disease. Mice were anesthetized, and their corneas were scratched and inoculated with virulent P. aeruginosa 6294 or PAO1, along with either 50 microg of oligosaccharide derived from LPS from P. aeruginosa PAC557 (complete outer core but no O side chains) or oligosaccharide derived from LPS of P. aeruginosa PAC1RalgC::tet (incomplete-core oligosaccharide). After 4 h, there were no differences between groups in the counts of infecting and internalized bacteria. At 24 h, the complete-core oligosaccharide decreased the levels of bacteria per eye by 70 to 99.7% compared with the levels achieved by including the incomplete-core oligosaccharide in the infectious inoculum. Epithelial cell ingestion of bacteria was comparably affected. However, the effect on disease was modest and only evident at lower challenge doses that elicited mild disease in controls and when the bacterial association and ingestion were inhibited by >99%. Overall, it appears that in the murine model of P. aeruginosa corneal infection at challenge doses of bacteria 10-fold or greater than the minimal amount needed to cause disease, the absolute level of inhibition of bacterial adherence is insufficient to reduce the bacterial counts below that which elicits disease.